Educação matemática encena - Lacerda, Hannah Dora de Garcia e [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research links drama and mathematics education, through a dialogue with the notion of Digital Mathematical Performances (DMPs), to answer the question: What images of mathematics and equations do students express when they develop mathematical theatrical performances? The activities were carried out with eighth and ninth grade students from a public school in Santa Gertrudes, SP. The activities consisted of introducing students to theatrical language, preparation and writing of a play about the mathematical content equations, as well as acting and filming them, with the goal of producing theatrical DMPs and posting them on the Internet. The work was based on the perspective of qualitative research methodology, and the procedures consisted of having a field notepad, focus groups, semi-structured interviews, participant observation and filming of gatherings. The mathematics images that students express are associated with the themes: school subject; changing the negative image of mathematics; daily life; reward; mathematical symbols. The issues related to students' images of equation were: letters, numbers and operations; balance/equality; the unknown; the rules. As final considerations, the potential of drama to change the image of mathematics and approaches to the DMPs, as well as the limitations encountered, and possibilities for future research are pointed out.

Esta pesquisa articula Teatro e Educação Matemática a partir do diálogo com a noção de Performances Matemáticas Digitais (PMDs), tendo como pergunta norteadora: quais as imagens sobre a Matemática e sobre equações estudantes expressam quando desenvolvem performances matemáticas teatrais? As atividades foram realizadas com alunos de oitavo e nono anos em uma escola pública de Santa Gertrudes, SP, e consistem em introdução à linguagem teatral, elaboração e escrita de uma peça teatral sobre o conteúdo matemático equações e encenação e filmagem da mesma, com o objetivo de produzir PMDs teatrais e publicá-las na internet. Tal trabalho foi fundamentado na perspectiva da Metodologia de Pesquisa Qualitativa, e os procedimentos consistiram em caderno de campo, grupo focal, entrevistas semiestruturadas, observação participante e filmagem dos encontros. A imagem que os estudantes expressam da Matemática estão associadas aos temas: disciplina escolar; transformação da imagem negativa; cotidiano; recompensa; símbolos matemáticos. Os temas referentes à imagem dos alunos sobre equação foram: letras, números e operações; balança/igualdade; incógnita; as regras. Como considerações finais são destacadas as potencialidades do Teatro na transformação da imagem da Matemática e aproximações com as PMDs, além das limitações encontradas durante o percurso e perspectivas de desdobramento dos questionamentos aqui propostos.
Mathematics Education Stages
Keywords: Digital mathematical performances; Equation; Public images of mathematics; Art; Teatro; Performance matemática digital; Equação; Imagem pública da matemática; Arte; Drama